2009
DOI: 10.1001/archgenpsychiatry.2009.104
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Amygdalar Subregion Functional Connectivity and Evidence of a Compensatory Network in Generalized Anxiety Disorder

Abstract: Our findings provide new insights into the functional neuroanatomy of the human amygdala and converge with connectivity studies in experimental animals. In GAD, we find evidence of an intra-amygdalar abnormality and engagement of a compensatory frontoparietal executive control network, consistent with cognitive theories of GAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

53
442
9
19

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 589 publications
(528 citation statements)
references
References 77 publications
53
442
9
19
Order By: Relevance
“…Further echoing earlier animal work, these iFC profiles were shown to undergo extensive age‐dependent changes, with BLA and CMA connectivity becoming increasingly segregated and specialized during the transition from adolescence to adulthood [Qin et al, 2012]. Importantly, and pertinent to the current study, these subregional iFC profiles seem relatively disorganized in psychiatric patients with emotion regulation deficits, suggesting impairments in various amygdala‐mediated functions [Aghajani et al, 2016; Etkin et al, 2009; Roy et al, 2013]. Despite the reputed amygdala dysfunction in psychopathy, though, little is known of how distinct traits of psychopathy might map onto BLA and CMA intrinsic connectivity, in people with clinical antisociality.…”
Section: Introductionsupporting
confidence: 80%
“…Further echoing earlier animal work, these iFC profiles were shown to undergo extensive age‐dependent changes, with BLA and CMA connectivity becoming increasingly segregated and specialized during the transition from adolescence to adulthood [Qin et al, 2012]. Importantly, and pertinent to the current study, these subregional iFC profiles seem relatively disorganized in psychiatric patients with emotion regulation deficits, suggesting impairments in various amygdala‐mediated functions [Aghajani et al, 2016; Etkin et al, 2009; Roy et al, 2013]. Despite the reputed amygdala dysfunction in psychopathy, though, little is known of how distinct traits of psychopathy might map onto BLA and CMA intrinsic connectivity, in people with clinical antisociality.…”
Section: Introductionsupporting
confidence: 80%
“…Roy et al, 2009 revealed that the CMA preferentially connects to subcortical brain regions, whereas the BLA preferentially connects to cortical regions in healthy adults. A study in social anxiety disorder patients showed increased gray matter volume in the CMA and less distinct connectivity patterns of the subregions (Etkin et al, 2009) compared with healthy controls. Stress-by-MR-blockade interaction on the connectivity between the centromedial amygdala and the caudate nucleus.…”
Section: Effects Of Mineralocorticoid Receptor Blocking In Humans S Vmentioning
confidence: 99%
“…Studies in rodents (Carbo-Gas et al, 2014a, Ikai et al, 1992, monkeys (Melchitzky and Lewis, 2000), and humans (Anderson et al, 2006) are indicative of dopaminergic synaptic components and transmission in the cerebellum across species. This evidence is accompanied by the fact that the cerebellar vermis has demonstrated to be linked to limbic and reward-related structures, such as amygdala (Sang et al, 2012;Yu et al, 2016), hippocampus (Sang et al, 2012), as well as ventral tegmental area (Rogers et al, 2011;Etkin et al, 2009;Kline et al, 2016;Kwon et al, 2014) and both dorsal (Tomasi and Volkow, 2011) ventral striatal zones (Cauda et al, 2011;Koehler et al, 2013). Accordingly, this part of the cerebellum could be able to integrate the incoming information from all these brain areas, which would encode the primary emotional and motivational aspects of the cue, to guide the response.…”
Section: The Cerebellum's Role: Craving or Prediction?mentioning
confidence: 99%
“…Concretely, co-activations and functional connections between cerebellum and cortical structures, such as dorsolateral prefrontal cortex (Habas et al, 2009;Leutgeb et al, 2016;Moulton et al, 2011;Sang et al, 2012), orbitofrontal cortex (Addis et al, 2016;Habas et al, 2009;Leutgeb et al, 2016), anterior cingulate cortex (Addis et al, 2016;Moulton et al, 2011;Sang et al, 2012;Zeng et al, 2012), insula (Addis et al, 2016;Habas et al, 2009;Moulton et al, 2011;Sang et al, 2012), and inferior frontal gyrus (Addis et , 2016;Moulton et al, 2011;Tomasi and Volkow, 2011) have been reported. Other subcortical structures such as amygdala (Leutgeb et al, 2016;Sang et al, 2012;Zeng et al, 2012), hippocampus (Onuki et al, 2015;Sang et al, 2012;Zeng et al, 2012), ventral tegmental area (Carnell et al, 2014;Etkin et al, 2009;Kline et al, 2016;Kwon et al, 2014), dorsal striatum (Moulton et al, 2011;Sang et al, 2012;Tomasi and Volkow, 2011), and ventral striatum (Cauda et al, 2011;Cservenka et al, 2014;Koehler et al, 2013) also have demonstrated to be connected to the cerebellum.…”
Section: Introductionmentioning
confidence: 99%